(untitled) (World Economics and Finance Bulletin, 2023)
This article explores strategies to improve the audit process for income and expenses in banks. By examining key aspects of the audit, including methodologies, results, and discussions, the article provides insights into enhancing the overall efficiency of financial audits in the banking sector